2023
DOI: 10.7759/cureus.37456
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Healthy Building Determinants With Musculoskeletal Disorders of the Extremities: A Systematic Review

Abstract: Musculoskeletal disorders (MSDs) are a substantial societal burden and various factors affect their causation, recovery, and prognosis. Management of MSDs is complex and requires multifaceted interventions. Given the challenges of MSDs and their continued burden, it is possible that additional elements could impact these disorders that have not been fully researched, for example, indoor environmental quality. Our previous review provided preliminary evidence that healthy building determinants (HBDs) are associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(18 citation statements)
references
References 113 publications
0
0
0
Order By: Relevance
“…Given the relationships of IAQ and breathing parameters with back pain and neck pain, along with the lack of clarity on which exercises are best for specific patients, it is plausible that interventions aimed at improving IAQ and breathing parameters, along with the array of other established risk factors, may be useful for reducing the risk of these disorders in public, residential, and workplace environments. While our previous reviews did not find any RCTs examining the efficacy of IAQ interventions on various MSDs [8,9], a recent systematic review found preliminary evidence from small randomized controlled trials (RCTs) to support the efficacy of breathing exercises on short-term pain measures for LBP [18]. Another systematic review on this topic uncovered one small RCT that assessed the independent effect of breathing exercises compared to non-breathing exercise control for LBP [19].…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…Given the relationships of IAQ and breathing parameters with back pain and neck pain, along with the lack of clarity on which exercises are best for specific patients, it is plausible that interventions aimed at improving IAQ and breathing parameters, along with the array of other established risk factors, may be useful for reducing the risk of these disorders in public, residential, and workplace environments. While our previous reviews did not find any RCTs examining the efficacy of IAQ interventions on various MSDs [8,9], a recent systematic review found preliminary evidence from small randomized controlled trials (RCTs) to support the efficacy of breathing exercises on short-term pain measures for LBP [18]. Another systematic review on this topic uncovered one small RCT that assessed the independent effect of breathing exercises compared to non-breathing exercise control for LBP [19].…”
Section: Introductionmentioning
confidence: 89%
“…The current review incorporated similar methods, evidence synthesis procedures, and reporting structure as our earlier reviews that examined HBDs and MSDs [8,9]. The current review was conducted and reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) [28] and other resources [1,12,[29][30][31][32][33][34] and was registered with PROSPERO (ID: CRD42022380515).…”
Section: Overviewmentioning
confidence: 99%
See 3 more Smart Citations